Comparative Studies of Photochemical and Electrochemical Methods on Mineralization of Picric Acid - Ingale, Sanjay Vishwasrao; Kumar, Ratanesh; Wagh, Pratap B; Joshi, K D (Defence Science Journal, 2022)
The effluents generated from synthesis and processing plant of Picric acid is reported to be carcinogenic and hence needs to be treated to reduce its concentration below safe discharge limit. Present paper deals with studies on mineralization of Picric acid by adopting photochemical and electrochemical processes and the efficacy of the both processes have been explored in details. Crucial process parameters viz. pH, concentration of oxidizer and catalyst for mineralization of Picric acid are optimized. In photochemical method, It is observed that Picric acid is treated to bring down its concentration from 100 ppm to ≤ 1 ppm under Photo-Fenton process in 2 hrs whereas same treatment carried out under Photo- catalytic process takes only 1 hr. It is also observed that TiO2 xerogel and beads of nano-TiO2 are more efficient compared to that of commercially available TiO2. The TiO2–Polysulfone (PS) beads show less efficiency than TiO2 xerogel. However, the Picric acid oxidation efficiency for TiO2–PS beads is comparable and advantage of TiO2–PS beads is that it can easily be recovered from the treated solution and can be reused in the next experiments. Electrochemical process is user’s friendly and economical. In case of electrochemical treatments at optimized process parameters under Electro-Fenton reaction picric acid is completely mineralized below its drain discharge limit where as under Electro-peroxide reaction picric acid is mineralized upto 3 ppm within 3 hrs. The treated solution has been characterized by using UV-Visible spectrophotometer, High performance Liquid Chromatography (HPLC) and Total Organic Carbon (TOC) Analyzer. The observed results have been interpreted and reported in the present paper.